THE EFFECT OF SCIENTIFIC INQUIRY LEARNING MODEL ASSISTED BY VIRTUAL LABORATORY TO STUDENT’S SCIENCE PROCESS SKILL ON DYNAMICS AND EQUILIBRIUM OF RIGID BODIES TOPIC - Maria Sitompul; Makmur Sirait (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2018)
The purposes of this research are to know student’s science process skills using scientific inquiry learning model on dynamics and equilibrium of rigid bodies topic,  to know student’s science process skills using conventional learning on dynamics and equilibrium of rigid bodies topic, to know the student’s activity based on science process skills indicator during the learning process using the scientific inquiry learning model, and to know the effect of scientific inquiry learning model on student’s science process skills on dynamics and equilibrium of rigid bodies topic. The  type of this research is quasi experimental which using pre-test and post-test design. The population are all of students of class XI SMAN 1 Perbaungan, consist of 4 classes. Two classes of them are used for the sample. Experiment class using scientific inquiry learning model and control class using conventional learning. The result of research shows that  the level of students’ science process skills in experiment class is a good criteria with the developed as the first meeting is 53.08, the second meeting is75.61, and the third meeting is 85.49. The average of pre-test in experiment class is 34.35 and in control class 34.53. The average of post-test in experiment class is 66 while in  control class  is 60. From one tail t-test can concluded there is influence of scientific inquiry learning model on students’ science process skills on dynamics and equilibrium of rigid bodies in class XI SMAN 1 Perbaungan.